Giới thiệu hướng tiếp cận Reggio Emilia và ứng dụng trong bối cảnh đổi mới giáo dục mầm non tại Việt Nam - Nguyễn , Thị Thành (Tạp chí Giáo dục, 2022)
Stemming from the requirements of the fundamental and comprehensive innovation in education and training in the context of globalization and international integration, early childhood education in Viet Nam currently seek breakthrough developments, especially teaching approaches in educational activities. This study shows that the Reggio Emilia approach is appropriate for the cause of reforming early childhood education in Vietnam. Applying this approach to learning projects for preschool children at Hoa Thuy Tien Practical Kindergarten has achieved positive results: children were active in discussing, interacting in groups and proposing ideas; creative in developing ideas and designing project activities; proud of the achievements. Teachers’ professional capacity and necessary pedagogical skills were improved. The cooperation between the school and parents was really effective. Thus, it can be affirmed that the application of the Reggio Emilia approach to preschool education innovation in Vietnam is currently the right direction, yielding encouraging results.